Polish E-Commerce Market and Its Evaluation - Maciej CZAPLEWSKI (Communications of International Proceedings, 2021)
Polish e-commerce with 30 percent increase in turnover and with the value of 15 billion EUR in 2020 is one of the most dynamically growing European markets. Despite the fact, that e-commerce in Poland is still only a small part of total retail sales compared to Western markets, the competition is increasing. Therefore, it is worth undertaking the task of presenting the current state of development of the e-commerce market in Poland as well as indicating possible possibilities for its further development. In order to do that author presented the characteristics of the Polish e-commerce supply side as well as the demand side. On one hand main market strategies of e-commerce sellers were described. On the other hand the basic behaviors and expectations of the consumer were also depicted. In the article the most recently available data on e-commerce in Poland were used. At the end some final remarks as well as some possible development directions of the Polish e-commerce market were made. Among others, the authors concluded that, achieving further e-commerce development in Poland will be possible especially in case of: developing new business models for e-commerce, further unification of international e-commerce regulation, including those within the EU, improving the safety of e-payments.
Keywords: e-commerce; Poland; e-business strategies.